ENERGY EFFICIENCY INVESTMENTS IN HOUSING - Bumelytė, Junona; Galinienė, Birutė; Markauskas, Ramūnas (Ekonomika, 2011)
Housing is at the core of the European Union’s prosperity as it is important to achieve energy saving targets and to combat climate change whilst contributing to energy saving and security. During the programming period 2007–2013, the European Union Cohesion Policy has started playinga new and important role in the process of supporting investments into energy efficiency measures in the housing sector. The increasing need for effective renovation of housing stock, which was constructed in the period when energy resources were cheap, is most notable in Central and Eastern Europe. The use of the European Union fund for the renovation of housing stock in Lithuania servers as a basis for assessing the impact of such investments on energy saving, natural gas import and greenhouse gas emissions.